Benefits left on the table: Evidence from the Servicemembers' Civil Relief Act. (October 2020) - Castleman, Benjamin L.; Patterson, Richard; Skimmyhorn, William
Abstract: In this study we test whether behaviorally-motivated informational interventions can lead individuals to utilize consumer financial protections. Specifically, we use a large-scale randomized controlled trial to test whether gain/loss framing and reminder messaging can lead servicemembers in the United States Army to utilize an interest-rate protection outlined in the Servicemember Civil Relief Act (SCRA). While we find that reminder messaging increases engagement with informational materials, we find no differences in engagement across gain and loss framing. Furthermore, we find that information provision has no effect on servicemember credit outcomes, regardless of how SCRA protections are framed or whether email reminders are sent. We run a second experiment to explore what factors may be limiting the efficacy of our interventions and find that low engagement with emails and significant attrition throughout the application process are likely to contribute to our results. Taken together, our results suggest that financial education or information interventions offered via email face significant challenges to their effectiveness even when the apparent benefits seem large.